Labour Income Uncertainty, Risk Aversion and Home Ownership - Luis Diaz-Serrano (Institute for the Study of Labor (IZA), 2004)
In this paper we investigate the effect of labour income uncertainty on the probability of home ownership in Germany and Spain. This study is motivated by two facts. Firstly, theoretical models provide ambiguous results in this issue. Secondly, there is limited previous empirical evidence and the existing focuses exclusively on the US housing market. We claim that more international evidence is necessary. To carry out this test we propose an income uncertainty measure based on panel data labour income equations. We observe that households facing increasing income uncertainty display preference for renting while those receiving positive transitory shocks in earnings tend to allocate them in property housing consumption. We also introduce the concept of ?skewness affection? as a relevant phenomenon in the housing tenure decisions. Income uncertainty analysis in housing decisions has important implications in the design of housing public policies and also in the design of mortgage insurance products.
Keywords: D1; J0; R0; 330; risk aversion; skewness affection; home ownership; labour income uncertainty; income shocks; Lohn; Risiko; Wohneigentum; Risikoaversion; Schätzung; Deutschland; Spanien